Keen interest and leadership talent reward Siti Aisyah with UMP Role Model Award - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) undergraduate, Siti Aisyah Darmawansyah, 23, was recently crowned “UMP Student Role Model”, for her unwavering interest and leadership role in many of the volunteer activities organized by the university.